2005
DOI: 10.1002/syn.20208
|View full text |Cite
|
Sign up to set email alerts
|

Galanin-mediated anxiolytic effect in rat central amygdala is not a result of corelease from noradrenergic terminals

Abstract: Galanin is colocalized extensively with norepinephrine in brain. Although this suggests possible activity-dependent neurotransmitter interactions, the functional significance of such colocalization remains elusive. Previously, we showed that enhancing stress-activation of the noradrenergic system by yohimbine pretreatment released galanin in central amygdala, attenuating the anxiety-like behavioral response to stress on the elevated plus-maze. The present study was conducted to determine, in this context, whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…This peptide, present in both dorsal raphe and locus coeruleus projecting to the frontal cortex and hippocampus has been implicated in both stress-related behavior as well as anxiety [22] e.g. from studies of the bed nucleus of stria terminalis located immediate adjacent to the central nucleus of amygdala [42]. On the contrary, we found that CCK-LI concentration was reduced in the frontal cortex postpartum by 26%.…”
Section: Discussioncontrasting
confidence: 63%
“…This peptide, present in both dorsal raphe and locus coeruleus projecting to the frontal cortex and hippocampus has been implicated in both stress-related behavior as well as anxiety [22] e.g. from studies of the bed nucleus of stria terminalis located immediate adjacent to the central nucleus of amygdala [42]. On the contrary, we found that CCK-LI concentration was reduced in the frontal cortex postpartum by 26%.…”
Section: Discussioncontrasting
confidence: 63%
“…There are many conflicting reports of the role of galanin in stress-related behavioral phenotypes, such as anxiogenic-like (Moller et al, 1999, Khoshbouei et al, 2002b, Echevarria et al, 2005, Swanson et al, 2005), anxiolytic-like (Bing et al, 1993, Holmes et al, 2002, Khoshbouei et al, 2002a, Barrera et al, 2006) or no effects (Karlsson et al, 2005, Kuteeva et al, 2005). The role of galanin in stress-related behaviors seems to be complex depending on the animal species, route and site of drug administration and behavioral paradigms employed (Lu et al, 2005b, Karlsson and Holmes, 2006, Rajarao et al, 2007), reflecting the complex galaninergic innervation in the CNS and the discrete yet partially overlapping patterns of the three galanin receptor subtypes (GalR1 – 3).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of Gal1, Gal2 and Gal3 receptors are expressed in amygdala (Branchek et al, 2000; Waters et al, 2000). Galanin administered into the ventricles is anxiolytic (Bing et al, 1993) and galanin infused directly into CeA reduces stress-induced anxiety (Khoshbouei et al, 2002; Barrera et al, 2006; but see Moller et al, 1999). Stressful stimuli release galanin (Weiss et al, 2005) and increase galanin mRNA in CeA (Palkovits et al, 2000).…”
Section: Central Amygdala Neuromodulators and Alcohol Dependencementioning
confidence: 99%